PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS KERUGIAN PENGISIAN BAHAN BAKAR MINYAK DI SPBU BUNGKUL KABUPATEN INDRAMAYU - Edi Wahjuni; Nuzulia Kumala Sari; Reston Sipta Sihite (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2022)
Business actors at the Bungkul gas station 34.45232 located on Jalan Soekarno Hatta, Bojong Sari Village, Indramayu Regency, West Java have been proven to have committed fraud in filling fuel oil at the gas station which was found by the Directorate General of Consumer Protection and Orderly Commerce. permissible error limit. Business actors in this case cause harm to consumers, consumer rights and protection issues. The use of measuring instrument technology in the business world is needed in the hope of satisfying consumers but in reality it causes many problems. There is an additional tool at the fuel measuring pump in the form of an electronic circuit to commit fraud. This practice results in harm to people who are not aware that they have been cheated while refueling. Various modes are carried out by the SPBU officers, one of which is by manipulating the measuring instrument at the gas station so that it seems as if the fuel that is served by the consumer is in accordance with the price paid. Business actors violate consumer rights, especially the right to obtain measurements, measurements, scales, comfort and safety in using goods and/or services. Then the method used is the statutory approach, the conceptual approach. The results of this study indicate that the Bungkul gas station must be responsible for providing compensation or compensation in the form of a refund of the amount that has been harmed. Keywords: Business actors, Consumers; Loss.